Advokasi Pemenuhan Hak Keselamatan Kerja melalui Penerapan APD: Studi Kasus Dinas Kebakaran dan Penyelamatan Kota Medan - Irwansyah Lubis; Iffah Adawiyyah; Windi Zahrani; Mufidah Harahap; Afiyah Tasya Husna (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine the advocacy of occupational safety rights through the implementation of Personal Protective Equipment (PPE) at the Medan City Fire and Rescue Service. This study involved firefighters and structural officials as informants, using a semi-structured interview method. The results of the study indicate that the availability of PPE is not evenly distributed, and the supervision of PPE use is less than optimal due to the absence of dedicated K3 officers. Although PPE has been provided according to standards, effective supervision remains a challenge. On the other hand, PPE usage training is integrated into daily operational activities, given the high frequency of fire incidents in Medan. Routine evaluations and learning from other cases play an important role in increasing awareness and compliance of officers in using PPE. This study emphasizes the importance of strict supervision, periodic evaluation, and the active role of leadership in building a strong occupational safety culture. These findings highlight the need for improved PPE distribution, more structured supervision, and continuous training to ensure the optimal safety of firefighters.